BOTnet_ACAC_2022_test_600K_MD - Ilyes Batatia; Simon Batzner; Dávid Péter Kovács; Albert Musaelian; Gregor N. C. Simm; Ralf Drautz; Christoph Ortner; Boris Kozinsky; Gábor Csányi (ColabFit, 2023)
Test set of decorrelated geometries sampled from 600 K xTB MD. Acetylacetone dataset generated from a long molecular dynamics simulation at 300 K using a Langevin thermostat at the semi-empirical GFN2-xTB level of theory. Configurations were sampled at an interval of 1 ps and the resulting set of configurations were recomputed with density functional theory using the PBE exchange-correlation functional with D3 dispersion correction and def2-SVP basis set and VeryTightSCF convergence settings using the ORCA electronic structure package.
Keywords: ColabFit; Dataset; AgPd_NPJ_2021; Materials Science; https://id.loc.gov/authorities/subjects/sh85082094.html; Machine Learning; https://id.loc.gov/authorities/subjects/sh85079324.html; Techniques/Computational Techniques/First-principles calculations; Techniques/Computational Techniques/Machine Learning; Techniques/Computational Techniques/Molecular Dynamics; Research Areas/Atomic & molecular structure/Potential energy surfaces; Research Areas/Electronic structure/Interatomic & molecular potentials